2008
DOI: 10.1186/1471-2164-9-248
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characteristics of microRNAs from Bombyx mori

Abstract: Background: MicroRNAs (miRNAs) are small RNA molecules that regulate gene expression by targeting messenger RNAs (mRNAs) and causing mRNA cleavage or translation blockage. Of the 355 Arthropod miRNAs that have been identified, only 21 are B. mori miRNAs that were predicted computationally; of these, only let-7 has been confirmed by Northern blotting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 59 publications
(57 reference statements)
3
50
1
Order By: Relevance
“…2E, the frequency of the four nucleotides (A, C, G and U) differed at each position. Previous studies have shown that animal mature miRNAs use U residues most frequently at their 5 0 end [33,34]. Our analysis of sequence characteristics at each position suggested that this trend is obvious for most of human mature miRNA sequences.…”
Section: Sequence Characteristics Of Different Lineage-specific Humansupporting
confidence: 53%
“…2E, the frequency of the four nucleotides (A, C, G and U) differed at each position. Previous studies have shown that animal mature miRNAs use U residues most frequently at their 5 0 end [33,34]. Our analysis of sequence characteristics at each position suggested that this trend is obvious for most of human mature miRNA sequences.…”
Section: Sequence Characteristics Of Different Lineage-specific Humansupporting
confidence: 53%
“…[21][22][23][24] More than 487 miRNAs have been identified in B. mori (miRBase release 21, June 2014), but their functions are only beginning to be understood. We show here that miR-2 and their target genes, abnormal wing disc (Bmawd) and fringe (Bmfng), mediate wing morphogenesis in this lepidopteron model insect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the silkworm genome has been reported in 2004, which provides opportunities for a thorough research for functional genomics (Xia et al, 2004). Because of the important functions of miRNA for gene regulation, our group firstly large-scale identified miRNA genes in Bombyx mori (He et al, 2008). Since then, due to the development of deep sequencing technology, a large number of miRNAs have been identified in silkworm (Cai et al, 2010;Huang et al, 2010;Liu et al, 2010b;Yu et al, 2008Yu et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%